Analisis Minat Menggunakan Produk Keuangan Syariah Serta Faktor yang Memengaruhinya - Khairunnisa, Citra; Hanifah, Nani (Jurnal Istiqro, 2025)
The presence of Islamic banks in the midst of conventional banking is to offer an alternative banking system for Muslims who need or want to obtain banking services without having to violate the prohibition on usury. The purpose of the study was to analyze how people's interest in using Islamic financial products and the factors that influence it. This research method uses a qualitative approach. The results of the study indicate that people's interest in using Islamic financial products is still quite low, some factors that influence it are the level of Islamic financial literacy, public perception of Islamic banks, and Islamic Branding.